INFLUENCING OF CHALLENGE BASED LEARNING MODEL TOWARD CRITICAL THINKING ABILITY OF THE STUDENTS ON ENVIRONMENT MATERIAL IN X GRADE AT SMA NEGERI 4 PRABUMULIH - Nurlaili Nurlaili; Dini Afriansyah; Yeni Atika Nuri (JURNAL PENA SAINS, 2017)
This study aims to determine the effect of learning model Challenge Based Learning on the critical thinking ability of environmental materials. The research method used in this research is a quasi-experiment with Non-Equivalent Control Group Design research design. Sampling was used by using purposive sampling technique. The sample of this study class X.2 as the experiment amounted to 20 and class X.3 as the control class amounted to 21 students. The results of this study indicate that the average N-gain of the experimental class is 0.61 which is in the medium category and the average N-gain for the control class is 0.24 which belongs to the low category. Data analysis using t-test with significant level 0,05 obtained tcount = 5,674 while ttable = 1,685 seen that tcount ttabel. Therefore (Ha) accepted and (H0) rejected thus can be concluded that the learning model of Challenge Based Learning has an effect on critical thinking ability of class X SMA 4 Prabumulih.